2013
DOI: 10.1128/aac.00708-13
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Humanized Carbapenem Exposures against New Delhi Metallo-β-Lactamase (NDM-1)-Producing Enterobacteriaceae in a Murine Infection Model

Abstract: Enterobacteriaceae producing the novel carbapenemase New Delhi metallo-␤-lactamase (NDM-1) are emerging worldwide. While these organisms often display high levels of in vitro resistance to multiple antibiotics, in vivo efficacy data are lacking. Here, the activities of humanized ertapenem and doripenem exposures were characterized against a wild-type K. pneumoniae and its derived isogenic strains harboring either an NDM-1 or KPC-2 plasmid in immunocompetent mice. In addition, four clinical isolates expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Unlike in vivo observations with isolates that produce the serine-carbapenemase KPC, carbapenem monotherapy has demonstrated reductions of NDM-1-producing bacterial isolates in a murine thigh infection model, even though the time that the concentration of an unbound antibiotic remains above the MIC during the dosing interval (ƒT ϾMIC ) needed for efficacy was not achieved for all of the isolates (10,11). Previous work by our group has demonstrated a reduction in bacterial density with human simulated monotherapy regimens of ertapenem and high-dose, prolonged infusion of doripenem against an isogenically constructed NDM-1-producing strain and four clinical NDM-1-producing strains in a murine thigh infection model (10).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike in vivo observations with isolates that produce the serine-carbapenemase KPC, carbapenem monotherapy has demonstrated reductions of NDM-1-producing bacterial isolates in a murine thigh infection model, even though the time that the concentration of an unbound antibiotic remains above the MIC during the dosing interval (ƒT ϾMIC ) needed for efficacy was not achieved for all of the isolates (10,11). Previous work by our group has demonstrated a reduction in bacterial density with human simulated monotherapy regimens of ertapenem and high-dose, prolonged infusion of doripenem against an isogenically constructed NDM-1-producing strain and four clinical NDM-1-producing strains in a murine thigh infection model (10).…”
mentioning
confidence: 99%
“…Previous work by our group has demonstrated a reduction in bacterial density with human simulated monotherapy regimens of ertapenem and high-dose, prolonged infusion of doripenem against an isogenically constructed NDM-1-producing strain and four clinical NDM-1-producing strains in a murine thigh infection model (10). Since these results were both surprising and promising, it is essential to validate them with additional in vivo studies before determining the potential clinical utility of carbapenems for treating infections caused by NDM-1-producing organisms.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Most interestingly, animal studies (mouse thigh infection) showed that both doripenem and ertapenem were effective against the metallo-b-lactamase (MBL) NDM-producing but not against KPC-producing K. pneumoniae isolates exhibiting similar levels of resistance to the latter drug (Wiskirchen et al, 2013(Wiskirchen et al, , 2014. Moreover, using the same animal model, increased doses of imipenem exhibited measurable bactericidal activity against K. pneumoniae resistant to the latter drug owing to production of another clinically important MBL, VIM-1 (Daikos et al, 2007).…”
mentioning
confidence: 99%